FACEBOOK® GROUP USAGE TO SUPPORT FLIPPED-CLASSROOM LEARNING ON OCULAR TRAUMA - Muhamad Reza Utama; Deny Yuliawan; Yoyo Suhoyo; Widyandana Doni (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2020)
Background: Facebook has been acknowledged as an alternative media in supporting traditional learning activities. However, its potential in enhancing students’ cognitive engagement on flipped-classroom’ activities is still not much known. This study aims to measure undergraduate medical students’ cognitive engagement changes after joining an ocular trauma flipped-classroom’ Facebook group.Methods: This pre-experimental study was involving 45 third-year undergraduate medical students of Muhammadiyah Surabaya' University who were joining the ocular trauma flipped-classroom' Facebook group. Three cognitive engagement variables were measured before students were joining the group and after the flipped-classroom’ face to face session ended. Finally, metrics data of the group members’ activities, which had been collected using Facebook Insight, used to shown changes between the active and passive user.Results: All users’ (n = 45) cognitive engagement were rising significantly after join the Facebook group (motivation, p = 0,000; self-directed learning readiness, p = 0,000; knowledge towards ocular trauma topic, p = 0,000). Increase in average active user knowledge was 11.09 points higher than passive users. Self-efficacy aspect of the students’ learning motivation and self-management aspects of the students’ self-directed learning readiness were the most increased sub-components.Conclusion: Facebook group has the potential to improve students’ cognitive engagement on ocular trauma’ flipped classroom.